Fournier's gangrene: outcome analysis of 62 consecutive cases. (July 2014) - El-Shazly, M; Sultan, M; Salem, S; Alkandari, I; Shebl, M
Objectives: The objective of this article is to study the outcome of management of 62 consecutive cases of Fournier's gangrene (FG). Patients and methods: We conducted an observational study of all cases of FG admitted to the Urology and General Surgery departments of Farwaniya Hospital, Kuwait, between 2004 and 2013. We recorded the laboratory and clinical findings on admission. Operative and postoperative data were also recorded. Results: Our study included 62 cases of FG. Patients were divided into two groups: Group A (survival) consisted of 55 cases and Group B (mortality) of seven cases. The mean duration of symptoms before admission was significantly longer in the mortality group (3.86 days versus 1.96 days in survival group) ( p < 0.05). The mean duration of symptoms until time of first debridement was also significantly longer in the mortality group (4.39 days versus 2.35 days in survival group) ( p < 0.05). There was also a statistically significant difference between the two groups regarding the percentage of the affected area in relation to total body surface area (4.6% in Group A versus 8% in Group B) ( p < 0.05). The Fournier Gangrene Severity Index score (FGSI) was significantly higher in Group B (10.26) in comparison to Group A (6) ( p < 0.01). The mean duration of hospital stay was significantly higher in the survival group (22.24 days versus 14.28 days) ( p < 0.01). Diabetes and renal failure were significantly higher in the mortality group (100% and 57.1% in Group B versus 54.5% and 9.1% in Group A, respectively) ( p < 0.05). The number of patients presenting with severe sepsis was higher in the mortality group (71.4% in Group B versus 12.7% in Group A) ( p < 0.05). Conclusion: We concluded that FG is a serious, potentially fatal disease. Higher mortality is related to severe sepsis on admission, renal failure, diabetes, extensive disease involving extra-genital areas and late presentation. A multidisciplinary approach in diagnosis and management of the disease can achieve good outcome with low mortality rate.